Penerapan Ontologi dalam Representasi Pengetahuan Gangguan Kesehatan Mental - Octavia, Hana Christine; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024, 2024)
Information about mental health disorders is widely available, but there is still a need for a system that can accommodate existing knowledge and assist experts in explaining this knowledge. Building an ontology using the methontology methodology involves 10 stages that must be followed to construct the ontology. The outcome of this research is expected to provide a clear and systematic representation of knowledge about mental health disorders based on the constructed ontology. This representation will aid in understanding, early diagnosis, and management of mental health disorders. The Protégé software is used for constructing this knowledge domain.